خطاب ما بعد الاستعمار في روايتي "مواكب الأحرار" لنجيب الكيلاني و"أسرة حرب العصابات" لبراموديا الإندونيسي : دراسة مقارنة - Amirul Hafiz bin Ali
Postcolonial discourse is an intellectual discourse under the field of Postcolonial Theory in Literature studies. It is one of the postmodernism's literary theories. The discourse tries to bring the discussion on literary discourse into prominence without depending on western thoughts that conquered literary fields and subjugate its principles in many instances. This study investigates the characteristics of postcolonial discourse, the discourse models, its contributions as well as the way it relates to narratives in novels. The aim of this study is to explore the nature of postcolonial discourse in Najib Al-Kilani's “Mawakib Al-Ahrar” and Pramoedya's “The Guerilla Family”. On that basis, the researcher analyses themes and critical issues in both novels in order to identify the postcolonial discourse that were brought up by both novelists in their respective novel. Then, the researcher also analyses the narrative techniques used by the novelists to demonstrate the issues to readers. Among the objectives of this study is to highlight the similarities and differences between the issues and techniques in both novels. Among the general findings of the study is that the issues in the novel “Mawakib Al-Ahrar” focus on the strives of Muslim Jihad (holy war) in resisting Napoleon's dominance; meanwhile the issues brought up in the novel “The Guerilla Family” circle around universal human quality in society under colonial power due to the writer's affiliation to socialist realism ideology in literature. Both novels exhibit different approaches in addressing postcolonial discourse.